Surface plasmon-enhanced Ag/CuS nanocomposites for cancer treatment - Yang, Chang (Cancer Nanotechnol, 2013)
Photothermal therapy (PTT) for cancer treatment is the use of heat between 41 and 45 °C to damage cancer cells. As a new type of transducer agent for PTT of cancer, CuS nanoparticles have several advantages. The most favorable features are the low cost, simple, and easy preparation and small size for targeting. However, the CuS nanoparticle PTT efficacy needs to be improved for practical applications. In this study, the CuS nano-PTT efficiency is enhanced via the local field enhancement from Ag nanoparticle surface plasmon coupling. The results show that absorbance of CuS nanoparticles in Ag/CuS nanocomposites is enhanced about four times by Ag nanoparticle surface plasmon coupling. Consequently, the PTT efficacy is enhanced and a power of 0.6 W/cm(2) with a 980-nm laser is sufficient for Ag/CuS nano-PTT activation for cancer treatment in vitro observations.